-Orthomorphisms and -Linear Operators on the Order Dual of an -Algebra Revisited - Jamel Jaber (Abstract and Applied Analysis)
We give a necessary and sufficient condition on an -algebra for which orthomorphisms, -linear operators, and -orthomorphisms on the order dual are the same class of operators.